2021
DOI: 10.1021/acsami.1c00864
|View full text |Cite
|
Sign up to set email alerts
|

Knittable and Sewable Spandex Yarn with Nacre-Mimetic Composite Coating for Wearable Health Monitoring and Thermo- and Antibacterial Therapies

Abstract: The emerging personal healthcare has significantly propelled the development of advanced wearable electronics with novel functions of providing diagnostic information and point-of-care therapies for specific diseases. However, it is still challenging to simultaneously achieve high sensitivity for health biomonitoring and multifunction integration for pointof-care therapies in a one single flexible, lightweight yet robust fiber-based device. Here, a knittable and sewable spandex yarn with conductive nacremimeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 70 publications
0
43
0
Order By: Relevance
“…In fact, previous studies have confirmed the interaction of single‐layer and multilayer MXene flakes with bacteria operating under the proposed mechanisms. [ 30 ] Therefore, the following features could be assumed: i) the hydrophilic nature of MXene in CHs (shown in Figure 3c) can improve the bacterial contact with the surface, resulting in the capture of bacteria, ii) the physical destruction of the bacterial cell wall or the outer membrane due to the presence of the MXene, iii) as occurs with montmorillonite layered aluminosilicate, the MXene nanosheets exhibit strong adsorption for bacteria. Furthermore, the AuNPs loaded in sMX also improved the bactericidal efficiency of S. aureus , probably due to the tension of the bacterial membrane affected by the with the AuNPs leading to the breakdown and death of the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, previous studies have confirmed the interaction of single‐layer and multilayer MXene flakes with bacteria operating under the proposed mechanisms. [ 30 ] Therefore, the following features could be assumed: i) the hydrophilic nature of MXene in CHs (shown in Figure 3c) can improve the bacterial contact with the surface, resulting in the capture of bacteria, ii) the physical destruction of the bacterial cell wall or the outer membrane due to the presence of the MXene, iii) as occurs with montmorillonite layered aluminosilicate, the MXene nanosheets exhibit strong adsorption for bacteria. Furthermore, the AuNPs loaded in sMX also improved the bactericidal efficiency of S. aureus , probably due to the tension of the bacterial membrane affected by the with the AuNPs leading to the breakdown and death of the bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…However, exposure to high humidity or air may cause the oxidation of MXene, thereby reducing its various properties, especially electrical properties [16,49]. For example, Gong et al developed a spandex composite yarn sensor with a composite coating using MXene nanosheets as "bricks" and PDA/Ni 2+ as "mortars" through alternate dip-coating methods [69]. The yarn strain sensor has high sensitivity, a low detection limit (0.11%) and a wide sensing range (0.11-61.2%).…”
Section: Mxenementioning
confidence: 99%
“…Flexible strain sensors are attractive for their light weight, good stretchability, and most importantly, the unique ability to convert external stress into electrical signals, thus having a great application potential in new-generation intelligent electronics, such as soft robotics, [1,2] human-machine interfaces [3,4] and personal health monitoring devices, [5,6] etc. According to different working principles, flexible strain sensors can be classified into piezoelectric type, [7,8] capacitive type, [9,10] and piezoresistive type.…”
Section: Introductionmentioning
confidence: 99%